Effect of Mental State on the Rate of Identifying the Relevancy of Documents Retrieved in a Search - Faezeh Farhoudi (Iranian Journal of Information Processing & Management, 2009)
The present study investigates the link between various users’ mental state while searching information systems with the outcome of the resulting documents retrieved. Various factors such as user knowledge, search skills, motivation and aims influence the decisions and evaluation of users regarding documents retrieved. MMPI instrument was used to identify users’ mental states. The sample was drawn from female senior students of librarianship, using systematic random sampling. The findings indicated that anxiety and depression have significant inverse relationship to the rate of relevancy identification of the documents retrieved by the users.